In situ STEM study on the morphological evolution of copper-based nanoparticles during high-temperature redox reactions. Issue 21 (21st May 2021) - Sharna, Sharmin; Bahri, Mounib; Bouillet, Corinne; Rouchon, Virgile; Lambert, Arnold; Gay, Anne-Sophie; Chiche, David; Ersen, Ovidiu
Abstract : Direct observation of the phase and morphological evolution of copper nanoparticles during oxidation (O2 ) and reduction (H2 ) reactions, as a function of temperature, using in situ STEM under atmospheric pressure. Abstract : Despite the broad relevance of copper nanoparticles in industrial applications, the fundamental understanding of oxidation and reduction of copper at the nanoscale is still a matter of debate and remains within the realm of bulk or thin film-based systems. Moreover, the reported studies on nanoparticles vary widely in terms of experimental parameters and are predominantly carried out using either ex situ observation or environmental transmission electron microscopy in a gaseous atmosphere at low pressure. Hence, dedicated studies in regards to the morphological transformations and structural transitions of copper-based nanoparticles at a wider range of temperatures and under industrially relevant pressure would provide valuable insights to improve the application-specific material design. In this paper, copper nanoparticles are studied using in situ Scanning Transmission Electron Microscopy to discern the transformation of the nanoparticles induced by oxidative and reductive environments at high temperatures. The nanoparticles were subjected to a temperature of 150 °C to 900 °C at 0.5 atm partial pressure of the reactive gas, which resulted in different modes of copper mobility both within the individual nanoparticles and on the surface of the support. Oxidation at an incremental temperature revealed the dependency of the nanoparticles' morphological evolution on their initial size as well as reaction temperature. After the formation of an initial thin layer of oxide, the nanoparticles evolved to form hollow oxide shells. The kinetics of formation of hollow particles were simulated using a reaction-diffusion model to determine the activation energy of diffusion and temperature-dependent diffusion coefficient of copper in copper oxide. Upon further temperature increase, the hollow shell collapsed to form compact and facetted nanoparticles. Reduction of copper oxide was carried out at different temperatures starting from various oxide phase morphologies. A reduction mechanism is proposed based on the dynamic of the reduction-induced fragmentation of the oxide phase. In a broader perspective, this study offers insights into the mobility of the copper phase during its oxidation–reduction process in terms of microstructural evolution as a function of nanoparticle size, reaction gas, and temperature.